Tratamiento audiovisual noticias emitidos en el canal C6 de la ciudad de Babahoyo en el primer trimestre del 2019 - Cruz Macias, Ruty Masiel (2020)
The topic, Audiovisual treatment, news broadcast on the C6 channel of the city of Babahoyo in the first quarter of 2019.With the general objective, Analyzing the audiovisual treatment of news content broadcast on the C6 channel of the city of Babahoyo was studied. The city of Babahoyo in the first quarter of 2019. Therefore, this study the techniques of qualitative research, descriptive research, diagnostic and field research, also applied direct observation and structured interview where the results arrogated that takes a good treatment C6 news, as it is a good example of compliance and standards in professional ethics It aims to benefit the citizens of Babahoyense, since through the analysis of the news audiovisual pieces transmitted in the first quarter of 2019 of the Channel C6, the contribution that has such content and how it influences the day-to-day, concluding with the project was feasible, it led us to know how a good management of the Audiovisual treatment is carried out.